An impact of tax reforms on the economic development in Uzbekistan - Maksudov Sherzod Ravshanbayevich (Zien Journals, 2022)
As an independent state, Uzbekistan appeared on the world map in 1991. The country launched reforms that were supposed to create a base for running a market economy. In 1996, however the course of the economy was radically shifted towards intensification of state intervention in the economy and the implementation of an import substitution policy. To accelerate industrial development, the state redistributed huge flows of material, financial, monetary and labour resources through: Direct allocation of resources, administrative regulation of commodity prices, interest rates and exchange rates; High taxes and government expenditures; Restricted access to the official exchange rate which is beneficial for currency buyers (usually two to three times different from the market rate); Establishment of artificial monopolies by limiting the access to markets for new players and provision of tax, credit and other benefits to certain enterprises or groups of enterprises; Direct (‘manual’) business management; and Limitation of imports by tariff and non-tariff barriers
Keywords: Tax; reforms; economic; economy